TANGGUNG JAWAB PERUSAHAAN ASURANSI ATAS PEMBATALAN PERJANJIAN BAKU PADA POLIS ASURANSI JIWA di KOTA DENPASAR - Hita Kartika Sari, Kadek; Agung, I Gusti Nyoman; Markeling, I Ketut (Kertha Wicara : Journal Ilmu Hukum, 2013)
In their life humans always faced with risk, something that threaten their life and make them suffer losses, the risk can be losing of life, losing moen, accident, fire and many other. To reduce that risk people can use insurance. The purpose of insurance is to cover the loss from an event that cann’t be predicted before. Insurance company use a standard contract in their contract. The usage of fixed agreement in their contract is against abolition of agreement.
Keywords: abolition, standard contract, polis and life insurance